Duplication of the superficial femoral artery: comprehensive review of imaging literature and insight into embryology. (July 2016) - Hapugoda, Sachintha; Hsu, Charlie Chia-Tsong; Kwan, Gigi Nga Chi; Watkins, Trevor William; Rophael, John A
An extremely rare case of duplicated superficial femoral artery (SFA) was incidentally observed on computed tomography angiogram (CTA) of the lower limbs for presurgical planning for an osteomyocutaneous fibula flap in a patient with T4a oropharyngeal squamous cell carcinoma (SCC). To our knowledge, this is the sixth reported case in the imaging literature. We performed a comprehensive review of the English literature and discuss the underlying embryological origin underpinning this rare anatomical variant.